A Chemical Photo‐Oxidation of 5‐Methyl Cytidines. Issue 20 (22nd August 2019) - Jin, Xiao‐Yang; Wang, Rui‐Li; Xie, Li‐Jun; Kong, De‐Long; Liu, Li; Cheng, Liang
Abstract: A new approach for the oxidation of 5‐methyl cytidine modification in nucleic acids to 5‐formyl cytidine is reported. This method displays excellent chemo‐/bio‐ selectivity, from which the methyl group in cytidine nucleosides could be selectively oxidized to biologically important formyl functionality without interfering with other cellular biomolecules. Abstract :